Plodnost jako přehlížené téma: Fertility as an Ignored Topic - Sokol, Jan (Lidé města, 2006)
Emmanuel Lévinas in some of his works, namely in Totality and Infinity, outlines entirely original philosophical anthropology. Let’s first review the most important Lévinas’s amendments and revisions relating to the philosophy of existence. Then, we shall focus on Fertility, the principal phenomenon not only for the Lévinasian anthropology and ontology, but also for secular ethics. Following exposition and detail interpretation of the Fertility Chapter of his Totality and Infinity, a chapter very dense and rich in content, we shall review the fact that this entirely principal topic of Western thinking – until Lévinas – was generally neglected or ignored.